Development of Optical Fiber Sensor for Blood Types Classification - Razali, Muhammad Hasif Hilmi; Wan Zaki, Wan Suhaimizan (Evolution in Electrical and Electronic Engineering, 2023)
Prior to giving a blood transfusion in an emergency situation, blood type determination is crucial. Currently, technicians must do these checks manually, which is prone to human error. It is crucial to accurately and quickly determine the blood types without human mistakes. In order to identify abnormal blood grouping in the human body, a technique based on classification blood grouping has been created. A LED is activated by the analogue input, and the LED then transmits light through fiber optic Using optical fiber connections, the LED’s light pulses are made to fall on blood samples. There will be matching voltage differences in the light detector’s output due to the optical variances of the various blood groups. As a result, we can quickly determine the blood by each of their group which is A, B, AB, and O